1982
DOI: 10.1093/jn/112.7.1379
|View full text |Cite
|
Sign up to set email alerts
|

Starvation-Induced Ketone Body Production in the Conscious Unrestrained Miniature Pig

Abstract: The effects of short-term starvation (up to 5 days) on hepatic ketone body production was investigated in the conscious unrestrained miniature pig in vivo. Starvation induced an increase in arterial free fatty acid concentration (0.2-0.7 mM) with a concomitant elevation in hepatic free fatty acid extraction [-1.4-5.7 mumol/kg. minute),r = 0.53, P less than 0.005]. Ketone body production (sum of acetoacetate + beta-hydroxybutyrate) increased from 1.5 to 5.8 mumol/(kg . minute) in parallel (r = 0.71, P less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…3). Infusion of Na-DL-13-OHB (15 gmol/kg X min) led to a drop in blood glucose, R. (-50%), and Rd (-45%). The effects were statistically significant at the beginning of the infusion period, and alterations were observed for up to 135 min perfusion time.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…3). Infusion of Na-DL-13-OHB (15 gmol/kg X min) led to a drop in blood glucose, R. (-50%), and Rd (-45%). The effects were statistically significant at the beginning of the infusion period, and alterations were observed for up to 135 min perfusion time.…”
Section: Methodsmentioning
confidence: 96%
“…14 male castrated miniature pigs (specific pathogen free, 28-32 kg body wt, 12-mo-old) were purchased (Versuchsgut Domane Relliehausen, Gottingen, Federal Republic of Germany) about 4 wk before the experiments were started. The pigs were held under controlled conditions and kept on a standard chow diet as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As ketone bodies are the result of partial free fatty acid oxidation, no differences in fatty acid oxidation would be expected between pig breeds at the hepatic level. In vivo, early studies with starved miniature pigs (Müller et al, 1982) suggested that mild ketosis encountered was modulated by insulin and glucagon. Indeed, similarly to the present experiment, where glucagon stimulated and insulin inhibited BHB production, it has been reported that ketone bodies synthesis in hepatocytes from 60 kg BW pigs are sensitive to long-term regulation by insulin, glucagon and dexamethasone (Fernández-Fígares et al, 2004), while short-term glucagon addition has been shown to have no effect on ketogenesis in pig hepatocytes (Pégorier et al, 1982).…”
Section: Bhb Synthesismentioning
confidence: 99%